Pengaruh Kompensasi, Lingkungan Kerja dan Jenjang Karir Terhadap Turnover Intention Karyawan pada PT. Mitra Tsunami Marine - Riska Nursaifah; Sari, Tika Nirmala (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
The purpose of this study is to determine and analyze the influence of compensation on turnover intention, to determine and analyze the influence of work environment on turnover intention, to determine and analyze the influence of career path on turnover intention, and to determine and analyze the simultaneous influence of compensation, work environment, and career path on turnover intention at PT. Mitra Tsunami Marine. The type of research used in this study is quantitative with an associative approach. with a sample of 90 respondents selected using the Slovin formula. The data collection technique used in this study was a questionnaire. The results of the study indicate that, partially, compensation, work environment, career path has a negative and significant influence on turnover intention. Simultaneously, compensation, work environment, and career path have a significant influence on turnover intention at PT. Mitra Tsunami Marine.